2019
DOI: 10.3390/su12010156
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Local Climate Zones in Abu Dhabi with Urban Weather Stations and Numerical Simulations

Abstract: In many cities that have experienced rapid growth like Abu Dhabi, urban microclimate scenarios evolve rapidly as well and it is important to study the urban thermal dynamics continuously. The Local Climate Zone (LCZ) classification considers factors related to the physical properties like surface cover and surface structure of the city which allow to analyze urban heat flows. Abu Dhabi city is rapidly expanding and is characterized by highly heterogeneous types of built forms that comprise mainly of old mid-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Considering the methodological application in other locations [36][37][38], Bragança (Portugal) was chosen as the study area for this work because it has the following characteristics: (i) there are no previous studies using RS data to analyze the LST at the site; (ii) it has the previous classification of Bragança in Local Climate Zones (LCZ) and UHI studies considering data from air temperature measured by the sensor network (Ta SN ) [23,32,39], that can be used to validate the data obtained in RS; (iii) its mountainous configuration can influence the circulation and speed of winds corroborating, naturally, to the formation of the UHI; (iv) presence of centralized urban densification with surrounding rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the methodological application in other locations [36][37][38], Bragança (Portugal) was chosen as the study area for this work because it has the following characteristics: (i) there are no previous studies using RS data to analyze the LST at the site; (ii) it has the previous classification of Bragança in Local Climate Zones (LCZ) and UHI studies considering data from air temperature measured by the sensor network (Ta SN ) [23,32,39], that can be used to validate the data obtained in RS; (iii) its mountainous configuration can influence the circulation and speed of winds corroborating, naturally, to the formation of the UHI; (iv) presence of centralized urban densification with surrounding rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…This city has heterogeneous surfaces, including building forms, and because it is in a coastal region in a desert environment, there are specificities in heat exchange. The study evaluated the UHI and seasonality in different seasons and times of the day and identified that the average temperature values, calculated throughout the day, pointed out the presence of UHI in different zones, especially in the densely urbanized ones 38 . Other studies associate LCZ classifications as a tool to assess the influence of LST distribution and UHI/SUHI effect on specific surfaces and have identified that the temperature was higher in densely urbanized areas [39][40][41][42][43] .…”
Section: State Of the Artmentioning
confidence: 99%
“…The zones are differentiated based on surface cover, material, structure and human activity. The LCZ classification can be used as an input for urban micro-climate models [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used the World Urban Database and Portal Tool (WUDAPT) platform for analysing climate zones in cities like Xi'an, China; Katuna, Nigeria; the London metropolitan area, UK etc. [5][6][7]. The interaction of these zones are linked to studying various topics, such as pollution, city expansion, UHI etc.…”
Section: Introductionmentioning
confidence: 99%